OR and ICU teams ‘running in parallel’ at the end of cardiothoracic surgery improves perceptions of handoff safety - Safraz Hamid; Frederic Joyce; Aaliya Burza; Billy Yang; Alexander Le; Ahmad Saleh; Robert S Poston (BMJ Open Quality)
The transfer of a cardiac surgery patient from the operating room (OR) to the intensive care unit (ICU) is both a challenging process and a critical period for outcomes. Information transferred between these two teams—known as the ‘handoff’—has been a focus of efforts to improve patient safety. At our institution, staff have poor perceptions of handoff safety, as measured by low positive response rates to questions found in the Agency for Health Care Research and Quality (AHRQ) Hospital Survey on Patient Safety Culture (HSOPS). In this quality improvement project, we developed a novel handoff protocol after cardiac surgery where we invited the ICU nurse and intensivist into the OR to receive a face-to-face handoff from the circulating nurse, observe the final 30 min of the case, and participate in the end-of-case debrief discussions. Our aim was to increase the positive response rates to handoff safety questions to meet or surpass the reported AHRQ national averages. We used plan, do, study, act cycles over the course of 123 surgical cases to test how our handoff protocol was leading to changes in perceptions of safety. After a 10-month period, we achieved our aim for four out of the five HSOPS questions assessing safety of handoff. Our results suggest that having an ICU team ‘run in parallel’ with the cardiac surgical team positively impacts safety culture.